Data przesłania tekstu do redakcji: 14.11.2013 Data przyjęcia tekstu do druku: 15.04.2014 Marina Protrka Štimec mprotrka@ffzg.hr Život kao artefakt: Matoševo autorstvo Povodom knjige Dubravke Oraić Tolić Čitanja Matoša - Protrka Štimec, Marina (Array, 2014)
Paper deals with a conception of Antun Gustav Matoš authorship, regarding his own definition of his life as a work of art. Performing his authorship in a variety of literary texts, letters and notices, he lived in extremes, being flaneur, dandy and a bohem, world traveler and a nationalist ideologist, what influenced reception of his work until recent period. Critical and historiographic, as much as other literary works related to AGM follow this „author-centered” posi- tions regarding his life as a work of art, as much as his literary texts as a reflection of his life. Latest Croatian „Matosiana” book, Dubravka Oraić Tolić Reading Matoš ( Čitanja Matoša , 2013), attests some traditional critical assumptions regarding authorship of this canonical writer end expands them in a new context. Different theories of literary canon formation, especially those grounded on feminist or psychoanalytical approach, call in question usual strategies in creation and understanding AGM s authorship, aestheticism and anti-modernism.